Nanostructural changes upon substitutional Al doping in ZnO sputtered films. Issue 5 (1st April 2019) - Landa-Cánovas, A.R.; Santiso, J.; Agulló-Rueda, F.; Herrero, P.; Navarrete-Astorga, E.; Ochoa-Martínez, E.; Ramos-Barrado, J.R.; Gabás, M.
Abstract: Al:ZnO layers, with low and high Al content, 0.2% and 2.1% cat. respectively, have been prepared using the RF magnetron sputtering technique. Noticeable differences in the optical and electrical properties have been detected in these films. With doping, the resistivity decreases and the band-gap increases. The alterations in the films crystalline structure are explained in terms of the nanostructural changes induced by Al substitutional doping, such as a higher concentration of edge dislocation defects and a higher rotation of crystalline nanodomains in the plane of the films (normal to the preferential orientation c -axis) for the high content Al:ZnO layer. A complete description of such effects has been accomplished using several characterization techniques, such as X-ray diffraction, Raman spectroscopy and transmission electron microscopy. The combination of these techniques provides an exhaustive understanding of the films nanostructure.